(untitled) (Al-Academy, 2020)
The scientific and technological developments and their practical applications in all fields of life in general and in the education field in specific have led to the emergence of variables in the educational structure, teaching methods and in education in their modern form which is consistent in its entirety with the spirit of the age. We today live the age of knowledge increase full of wide ranging scientific and technological developments. Thus life demands human capabilities of a special kind able to develop and innovate. Here the increasing significance emerges for taking care of the human powers through educational systems much different from those current traditional systems. Systems that address human intelligence in general and the visual intelligence in specific. Because the most important intelligence processes come directly from our visual perception of the world around us, where sight becomes the first sensory system that provides the basis of our cognitive processes and form them. Thus visual intelligence has become a primary goal that must be at the front of our educational goals for any teaching subject, and specifically the subject of art education. The objective of the current research is to construct a means for measuring the attitude towards visual intelligence because it is not available. Identifying the attitudes of the male and female teachers of art education towards visual intelligence in teaching and identifying the differences between the two sexes in using visual intelligence. In the light of the results, the researcher recommended training the teaching staff on the use of visual intelligence strategy in teaching art education and boosting the ways and means sufficient to develop the positive attitudes of the male and female teachers of art education towards the use of the visual intelligence